Role of Transient Receptor Potential Vanilloid 4 in Vascular Function - Liu, Liangliang; Guo, Mengting; Lv, Xiaowang; Wang, Zhiwei; Yang, Jigang; Li, Yanting; Yu, Fan; Wen, Xin; Feng, Lei; Zhou, Tingting (Frontiers in Molecular Biosciences, 2021)
Transient receptor potential vanilloid 4 (TRPV4) channels are widely expressed in systemic tissues and can be activated by many stimuli. TRPV4, a Ca2+-permeable cation channel, plays an important role in the vasculature and is implicated in the regulation of cardiovascular homeostasis processes such as blood pressure, vascular remodeling, and pulmonary hypertension and edema. Within the vasculature, TRPV4 channels are expressed in smooth muscle cells, endothelial cells, and perivascular nerves. The activation of endothelial TRPV4 contributes to vasodilation involving nitric oxide (NO), prostacyclin (PGI2), and endothelial-derived hyperpolarizing factor (EDHF) pathways. TRPV4 activation also can directly cause vascular smooth muscle cell (VSMC) hyperpolarization and vasodilation. In addition, TRPV4 activation can evoke constriction in some specific vascular beds or under some pathological conditions. TRPV4 participates in the control of vascular permeability and vascular damage, particularly in the lung capillary endothelial barrier and lung injury. It also participates in vascular remodeling regulation mainly by controlling vasculogenesis and arteriogenesis. This review examines the role of TRPV4 in vascular function, particularly in vascular dilation and constriction, vascular permeability, vascular remodeling, and vascular damage, along with possible mechanisms, and discusses the possibility of targeting TRPV4 for therapy.